Role of dental health professional in tobacco cessation: a review - Gurung, Deepak; Bhardwaj, Vinay K.; Fotedar, Shailee; Thakur, Arun S. (International Journal Of Community Medicine And Public Health, 2022)
Dental health professionals are large untapped resource, still have not been utilized to its full capacity. Even brief chair side-based interventions can come a long way in motivating and assisting tobacco users to quit. Many studies have highlighted the potential barriers in utilization of dental health professional to their full potential and capacities in tobacco cessation. Continuous repeated emphasis on incorporation of tobacco cessation training at the undergraduate level and after completion of dental degree is important. Much has been focused in the first three of 5A’s in the previous years. Step are needed to prioritize tobacco cessation activities focusing in last two (assists and arrange) of 5A’s in the coming years to come. The present study tries to understand the role of dental health professional and their contribution in controlling this global tobacco use problem. Understanding the multifaceted approaches to tobacco cessation by the dental health professionals so as to achieve higher “quit” rates and delivering of comprehensive counseling.